Pengaruh Terapi Emotional Freedom Technique (EFT) terhadap Depresi pada Klien Hipertensi - Mila Yuni Sahlia; wantiyah wantiyah; mulia hakam (Pustaka Kesehatan, 2018)
Hypertension is a disease that characterized by increased of systolic and diastolic bloodpressure that can cause problems in both physical and psychological problems. One ofpsychological problems is depression. EFT therapy is a relaxation technique that could beused to decrease depression in hypertension client. The purpose of this study was to analyzethe effect of EFT therapy on depression in hypertension client. This research usedquasi experimental method with control group pretest-posttest design. The sampling techniquewas consecutive sampling involving 20 respondents that divided into 10 respondentas intervention group who got EFT therapy and 10 respondents as control group who doneactivity daily. Data were analyzed by using Wilcoxon and Mann Whitney U Test with 95%CI (ɑ=0,05). The result showed that there was a difference of depression before given EFTin intervention group (p=0,003), while in control group there was no difference (p=1,000).There was significant difference of depression on client hypertension in both interventionand control group (p=0,001).The relaxation effect of EFT therapy stimulates the pituitarygland to release endorphin hormone to produce serotonin hormone and dopamine hormone.The conclusion is EFT therapy can reduce depression in hypertension clients, thereforeit can be applied as one of the non-pharmacological therapy in hypertension client. Keywords: EFT Therapy, Depression, Hypertension